2014
DOI: 10.1007/s11356-014-3358-x
|View full text |Cite
|
Sign up to set email alerts
|

Mining in New Caledonia: environmental stakes and restoration opportunities

Abstract: New Caledonia is a widely recognised marine and terrestrial biodiversity hot spot. However, this unique environment is under increasing anthropogenic pressure. Major threats are related to land cover change and include fire, urban sprawling and mining. Resulting habitat loss and fragmentation end up in serious erosion of the local biodiversity. Mining is of particular concern due to its economic significance for the island. Open cast mines were exploited there since 1873, and scraping out soil to access ores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 85 publications
1
70
0
2
Order By: Relevance
“…New Caledonia is also well known for its relative abundance of ancient lineages and the persistence of a suite of palaeoendemics (Pillon 2012), providing support for the Ocbil hypothesis concerning increased rarity and endemism, although New Caledonia's endemism may also be due to its insular nature. Additionally, the vegetation is highly sensitive to soil removal (Losfeld et al 2015), which is another prediction of Ocbil theory (Hopper 2009). …”
Section: New Caledoniamentioning
confidence: 93%
See 3 more Smart Citations
“…New Caledonia is also well known for its relative abundance of ancient lineages and the persistence of a suite of palaeoendemics (Pillon 2012), providing support for the Ocbil hypothesis concerning increased rarity and endemism, although New Caledonia's endemism may also be due to its insular nature. Additionally, the vegetation is highly sensitive to soil removal (Losfeld et al 2015), which is another prediction of Ocbil theory (Hopper 2009). …”
Section: New Caledoniamentioning
confidence: 93%
“…New Caledonia is a global biodiversity hotspot facing extreme environmental degradation due to land cover change, fire, urban sprawl and mining (Wulff et al 2013;Losfeld et al 2015). Pillon (2012) suggested that 'because of the abundance of low fertility soils, New Caledonia may be considered to be an old, climatically buffered and infertile landscape (OCBIL; Hopper 2009), similar to the Cape and to south-west Australia, but its climatic stability remains to be proven.'…”
Section: New Caledoniamentioning
confidence: 99%
See 2 more Smart Citations
“…With about 85% endemism among terrestrial plants, 24 different species of mangroves among the 70 listed throughout the world, about 2800 species of molluscs and the second longest barrier reef in the world [10][11][12][13][14][15], New Caledonia's ecosystems and biodiversity are highly sensitive to anthropogenic activities (e.g., [16][17][18][19][20][21][22][23] for its lagoons). Since the beginning of mining in New Caledonia, more than 160 × 10 6 tonnes of ore have been extracted.…”
Section: Introductionmentioning
confidence: 99%